Apakah Dewan Pengawas Syariah Berkontribusi pada Model Pendeteksian Kecurangan Vousinas? - Arifia, Annastasya Rizqi; Zulfikar, Zulfikar; Witono, Banu (LPPM, Universitas Islam Syarifuddin Lumajang, 2025)
This research examines the determinants of financial statement fraud in Islamic banks in Indonesia with multiple linear regression and moderated regression analysis (MRA). Based on data from 56 Islamic banks 2017–2020, this study investigates the influence of stimulus, ability, collusion, opportunity, rationalization, and ego on fraud with the moderating of Sharia Supervisory Boards (SSB). The results show that stimulus, rationalization and ego positively affect the financial statement fraud and capability, collusion and opportunity negatively affect the financial statement fraud. Furthermore, SSB substantially moderates the effect of collusion, opportunity, rationalization, and ego, hence validating its preventive role to curb fraudulent practices. The findings underscore the pivotal role of robust internal controls, ethical leadership, and sound governance in combating fraud in Islamic banking. The need to strengthen the oversight function of the SSB and enhance fraud detection mechanisms in the sector is critical to safeguarding the integrity of Islamic finance. This research contributes to the ongoing discourse on integrating Islamic ethical governance into contemporary risk and fraud detection models.